A new lossless passive snubber with simple structure for pulse width modulation DC-DC converters - vesali, mahmood (JAREE (Journal on Advanced Research in Electrical Engineering), 2023)
A new lossless passive snubber for pulse width modulation converters is introduced in this paper. This snubber is established zero current switching condition for main switch in the converters for turning on distance. This snubber does not impose any additional current stress on the switch. The snubber can be applied to all single-switch DC-DC converters. A boost converter with the proposed snubber is analyzed and to verify theoretical analysis a 200 W sample is implemented and tested, also the experimental results are presented. In order to investigate the effect of snubber circuit in the converter in terms of efficiency, the boost converter with the proposed snubber has been compared in terms of efficiency with the conventional boost converter and the results show that the efficiency has increased by about 7% despite the snubber.